Instant detection and identification of concealed explosive-related compounds: Induced Stokes Raman versus infrared. (January 2017) - Elbasuney, Sherif; El-Sherif, Ashraf F.
Highlights: We believe the manuscript describes a significant development relating to the art state of real-time identification of hidden explosives. Real-time identification of concealed explosive-related compounds. Stokes-Raman spectra with sharp intense characteristic peaks for concealed explosive-explosive related compounds. Comparative investigation of characteristic IR absorption and Stokes Raman scattering to certain molecular vibrations. Complete spectroscopic profile of explosive-related materials. Abstract: The instant detection of explosives and explosive-related compounds has become an urgent priority in recent years for homeland security and counter-terrorism applications. Modern techniques should offer enhancement in selectivity, sensitivity, and standoff distances. Miniaturisation, portability, and field-ruggedisation are crucial requirements. This study reports on instant and standoff identification of concealed explosive-related compounds using customized Raman technique. Stokes Raman spectra of common explosive-related compounds were generated and spectrally resolved to create characteristic finger print spectra. The scattered Raman emissions over the band 400:2000 cm −1 were compared to infrared absorption using FTIR. It has been demonstrated that the two vibrational spectroscopic techniques were opposite and completing each other. Molecular vibrations with strong absorption in infrared (those involve strong change in dipole moments) induced weak signals in Raman and vice versa. The tailored Raman offered instant detection, high sensitivity, and standoff detection capabilities. Raman demonstrated characteristic fingerprint spectra with stable baseline and sharp intense peaks. Complete correlations of absorption/scattered signals to certain molecular vibrations were conducted to generate an entire spectroscopic profile of explosive-related compounds. This manuscript shades the light on Raman as one of the prevailing technologies for instantaneous detection of explosive-related compounds.